The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1007/s00330-023-09595-z
|View full text |Cite
|
Sign up to set email alerts
|

Left ventricular myocardial strain responding to chronic pressure overload in patients with resistant hypertension evaluated by feature-tracking CMR

Abstract: Objectives The study aimed to investigate the alterations of myocardial deformation responding to long-standing pressure overload and the effects of focal myocardial fibrosis using feature-tracking cardiac magnetic resonance (FT-CMR) in patients with resistant hypertension (RH). Methods Consecutive RH patients were prospectively recruited and underwent CMR at a single institution. FT-CMR analyses based on cine images were applied to measure left ventricula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 37 publications
1
1
0
Order By: Relevance
“…In addition to the abnormality of the valvular structure itself, systemic hypertension is an important cause of chronic AR, but such patients do not necessarily receive additional attention in the absence of obvious clinical symptoms 18,19 . In this study, we found that in the absence of AR, hypertensive patients mainly showed a decrease in GLPS and diastolic peak strain rate, which was consistent with previous studies 10,20,21 . When complicated with AR, the radial and circumferential peak strain, as well as the peak systolic strain rates also decreased in patients with hypertension.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In addition to the abnormality of the valvular structure itself, systemic hypertension is an important cause of chronic AR, but such patients do not necessarily receive additional attention in the absence of obvious clinical symptoms 18,19 . In this study, we found that in the absence of AR, hypertensive patients mainly showed a decrease in GLPS and diastolic peak strain rate, which was consistent with previous studies 10,20,21 . When complicated with AR, the radial and circumferential peak strain, as well as the peak systolic strain rates also decreased in patients with hypertension.…”
Section: Discussionsupporting
confidence: 90%
“…18,19 In this study, we found that in the absence of AR, hypertensive patients mainly showed a decrease in GLPS and diastolic peak strain rate, which was consistent with previous studies. 10,20,21 When complicated with AR, the radial and circumferential peak strain, as well as the peak systolic strain rates also decreased in patients with hypertension. These results suggest that in addition to diastolic dysfunction, LV systolic dysfunction may also occur earlier in hypertensive patients with AR.…”
Section: Discussionmentioning
confidence: 99%